A hidden Amazonian fauna: first record of Neoempheria bilobata Edwards, 1940 (Diptera: Mycetophilidae) in Pará State, Brazil - Amaral, Edna Maria; Oliveira, Sarah Siqueira; Falaschi, Rafaela Lopes (EntomoBrasilis, 2022)
Neoempheria Osten Sacken is a genus of Mycetophilidae that has a life cycle associated with fungi. The genus is diverse in the Neotropical region, with 41 species known from Brazil that are predominantly known in southern and southeastern areas. This study reports on the first record of this genus for Pará state and redescribes Neoempheria bilobata Edwards, which was previously decribed from a male holotype from southern Brazil. We furnished high-resolution images and illustrations, as well as a detailed redescription of this species, based on male and female specimens.